PENDIDIKAN LITERASI MEDIA UNTUK GURU-GURU SMK MUHAMMADIYAh 2 PEKANBARU - Fitria Mayasari; Jupendri Jupendri; Jayus Jayus; Desliana Dwita (Jurnal Pengabdian UntukMu NegeRI, 2018)
The rapid development of television stations in Indonesia has influenced various aspects of people's lives such as among school students like in SMK Muhammadiyah 2 Pekanbaru. Various aspects influenced include social, cultural, religious, health and service quality. Social reality or the negative impact of the presence of mass media especially television does get the attention of parents and teachers. Media literacy education is one of the efforts to develop skills in selecting and watching critically the programs presented by the media. Media education or media literacy is an activity that can help people to have the competence, ability, or skill needed to not reactive in a negative sense, but proactive in understanding the messages conveyed by the media. Educators are the right audience for media literacy education. In an effort to provide understanding to school students in choosing, understanding and sorting media messages, especially television media. For that done community service activities in the form of Media Literacy Education For Teachers in SMK Muhammadiyah 2 Pekanbaru. The results of this activity, teachers in SMK Muhammadiyah 2 become more familiar about media literacy, and able to provide direction and understanding of the contents of the media so that learners become critical and creative. Keywords: media literacy, teachers, SMK Muhammadiyah 2